THE EFFECT OF INTELLECTUAL INTELLECTUAL AND SPIRITUAL INTELLIGENCE ON THE PERFORMANCE OF EMPLOYEES IN THE CAPITAL INVESTMENT SERVICE AND INTEGRATED SERVICES IN MAKASSAR CITY - Muh Nur Rasyid; Agussalim HR; Arnawati Arnawati (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine and analyze the Effects of Intellectual Intelligence and Spiritual Intelligence on the Performance of Employees of the Makassar City Investment and Integrated Service Office. Data analysis using multiple regression equations and the classic assumption test, one of the methods used to determine the number of samples is using the Slovin formula, the sample used was 50 employees. The research data was obtained from questionnaires, literature studies, and direct interviews with relevant parties according to the research objectives. From the results of multiple regression testing, data showing the variable Intellectual Intelligence and Spiritual Intelligence have a positive effect by looking at the F test value of 65.950, thus F arithmetic F table ( 0.05), For the t value of the intellectuality variable of 0.179 and the significance value of 0.112 0.05 so that the variable Intellectual Intelligence has a positive and insignificant effect, while the Spiritual Intelligence variable of 0,000 0.05 so the more positive and significant effect on employee performance is the Spiritual Intelligence variable